2020
DOI: 10.1055/s-0040-1712493
|View full text |Cite
|
Sign up to set email alerts
|

Lesões condrais maiores tratadas com uso de membrana de colágeno – Condrogênese autóloga induzida por matriz - Apresentam maior aumento nos escores clínicos

Abstract: Resumo Objetivo Avaliar clínica e radiologicamente os resultados do tratamento das lesões condrais com a membrana de colágeno – condrogênese autóloga induzida por matriz. Métodos Trata-se de uma série de casos observacional, na qual foram analisados 15 pacientes submetidos a condrogênese autóloga induzida por matriz. A avaliação clínica foi feita comparando os escores de Lysholm e International Knee Document Commitee (IKDC, na sigla em inglês) no pré- e pós-operatório de 12 meses, e avaliaç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…This allows for the release of bone marrow and blood, which then form blood clots to fill the defect site and promote fibrocartilage formation. However, it should be noted that these blood clots formed after MF lack sufficient mechanical resistance to remain in place [ 43 ]. In contrast, AMIC utilizes MF as part of a single-stage operation, followed by the application of a resorbable membrane over the treatment site.…”
Section: Discussionmentioning
confidence: 99%
“…This allows for the release of bone marrow and blood, which then form blood clots to fill the defect site and promote fibrocartilage formation. However, it should be noted that these blood clots formed after MF lack sufficient mechanical resistance to remain in place [ 43 ]. In contrast, AMIC utilizes MF as part of a single-stage operation, followed by the application of a resorbable membrane over the treatment site.…”
Section: Discussionmentioning
confidence: 99%
“…AMIC had a greater benefit in patients with larger chondral lesions evaluated per subjective clinical scores and magnetic resonance observation of cartilage repair tissue (MOCART). 29 Another study with 56 patients presenting single chondral or osteochondral lesions demonstrated that chondrocyte culture in fibrin could provide a favorable microenvironment for matrix synthesis, improving their clinical condition and activity after 1 year of follow-up. 30 …”
Section: Treatmentmentioning
confidence: 99%
“…No nosso meio, uma série de casos observacional analisando os resultados de 15 pacientes tratados pela técnica de AMIC (codrogênese autóloga induzida por matriz, usando membrana porcina de colágenos tipo I/III, evidenciou maior benefício em pacientes com lesões condrais de maior tamanho pela avaliação de escores clínicos subjetivos e pela avaliação radiológica pelo MOCART ( Magnetic Resonance Observation of Cartilage Repair Tissue ). 29 Outro estudo realizado com 56 pacientes apresentando lesões únicas condrais ou osteocondrais demonstrou que a cultura de condrócitos em fibrina poderia proporcionar um microambiente favorável para a síntese de matriz, melhorando a condição clínica e a atividade dos pacientes após um ano de acompanhamento. 30 …”
Section: Transplante Autólogo De Condrócitosunclassified
See 2 more Smart Citations